1998
DOI: 10.1172/jci1722
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and metabolic correction of pompe disease by enzyme therapy in acid maltase-deficient quail.

Abstract: Pompe disease is a fatal genetic muscle disorder caused by a deficiency of acid alpha-glucosidase (GAA), a glycogen degrading lysosomal enzyme. GAA-deficient (AMD) Japanese quails exhibit progressive myopathy and cannot lift their wings, fly, or right themselves from the supine position (flip test). Six 4-wk-old acid maltase-deficient quails, with the clinical symptoms listed, were intravenously injected with 14 or 4.2 mg/kg of precursor form of recombinant human GAA or buffer alone every 2-3 d for 18 d (seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(103 citation statements)
references
References 24 publications
2
97
0
4
Order By: Relevance
“…10 Long-term correction of GSD-II in GAA-KO/SCID mice F Xu et al GSD-II patients. 15,20 Recently, it has been demonstrated that restoration of a single muscle's contractile force can be achieved after intramuscular injection of an AAV vector encoding hGAA. 21 However, the evaluation of overall gross muscle strength has not been reported after attempting gene therapy using viral vectors in GSD-II animal models.…”
Section: Normalized Muscle Function After Extended Glycogen Clearancementioning
confidence: 99%
“…10 Long-term correction of GSD-II in GAA-KO/SCID mice F Xu et al GSD-II patients. 15,20 Recently, it has been demonstrated that restoration of a single muscle's contractile force can be achieved after intramuscular injection of an AAV vector encoding hGAA. 21 However, the evaluation of overall gross muscle strength has not been reported after attempting gene therapy using viral vectors in GSD-II animal models.…”
Section: Normalized Muscle Function After Extended Glycogen Clearancementioning
confidence: 99%
“…2 The prospect of enzyme therapy for GSD II highlights the immediate need for accurate figures on the frequency of the disease. 3,4 The figure of 1 in 100 000 normally quoted is not based on solid data. 1,5 Given present knowledge of the molecular genetics of GSD II, 1,2,6 and the genotype-phenotype correlation, 7,8 we now have the tools to update the meagre and aging data on the frequency of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials of ERT in MPS type VI patients are in progress (23). ERT in quails with acid-␣-glucosidase deficiency (glycogenosis type II) improved muscle function (25). In four infants with Pompe's disease, ERT resulted in improved cardiac structure and function and prolonged survival (26)(27)(28), but long-term results are not yet available.…”
mentioning
confidence: 99%